2014
DOI: 10.1155/2014/651259
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Is Not Associated with Incomplete Wireless Capsule Endoscopy for Inpatient or Outpatient Procedures

Abstract: Objective. Wireless capsule endoscopy (WCE) is commonly used to directly visualize the small bowel. Opioids have variably been linked with incomplete studies and prolonged transit times in heterogeneous cohorts. We aimed to investigate the effect of opioid use on WCE for inpatient and outpatient cohorts. Methods. We performed a retrospective review of patients receiving WCE at our institution from April 2010 to March 2013. Demographic data, medical history, and WCE details were collected. Transit times were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…We found that the use of narcotic medication was associated with incomplete VCE. This is in contrast to our previously published experience and has been found to be of variable significance in other studies 5 16 17 . Diabetes mellitus type 2 was also found to be significantly associated with incomplete VCE.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that the use of narcotic medication was associated with incomplete VCE. This is in contrast to our previously published experience and has been found to be of variable significance in other studies 5 16 17 . Diabetes mellitus type 2 was also found to be significantly associated with incomplete VCE.…”
Section: Discussioncontrasting
confidence: 99%
“…This is remarkable as BMI is not included as a clinical characteristic in most other series assessing completion rates and may be an uncontrolled factor affecting previously published results. To our knowledge, the series by Spada et al assessing bowel transit times during VCE in patients with Celiac disease and the work by our group assessing opioid use and VCE completion, are the only studies to include BMI as a variable 15 16 . Neither study reported a significant correlation but both are limited by a retrospective study design.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has been shown to be a risk factor for poor colon preparations, though the effects of diabetes on CE preparation are poorly characterized[28]. Likewise, our study included a large percentage of current opioid users at 28.1%; however opioid use has not clearly been shown to be associated with altered exam completion rates or diagnostic findings[29,30].…”
Section: Discussionmentioning
confidence: 99%